2015
DOI: 10.1117/1.nph.2.1.015006
|View full text |Cite
|
Sign up to set email alerts
|

Rat embryonic hippocampus and induced pluripotent stem cell derived cultured neurons recover from laser-induced subaxotomy

Abstract: Abstract. Axonal injury and stress have long been thought to play a pathogenic role in a variety of neurodegenerative diseases. However, a model for studying single-cell axonal injury in mammalian cells and the processes of repair has not been established. The purpose of this study was to examine the response of neuronal growth cones to laser-induced axonal damage in cultures of embryonic rat hippocampal neurons and induced pluripotent stem cell (iPSC) derived human neurons. A 532-nm pulsed Nd∶YVO 4 picosecond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…To ensure that we were quantifying staining in axons and not dendritic processes, we made use of microfluidic compartments, which separate axons from the bulk somatodendritic population (Figure 1E) (Niederst et al, 2015; Selfridge et al, 2015; Taylor et al, 2006). Neurons grown in microfluidic devices extend long processes into the axonal space that do not stain for the somatodendritic marker Map2 and that do stain for the axonal marker neurofilament-H (SMI31) (Selfride et al, 2015) (Figure 1E and Figure S1A). We observed that PS1 ΔE9 axons grown in microfluidic devices have decreased axonal APP puncta and APP puncta intensity (Figure 1D); this decrease is sensitive to PS1 ΔE9 gene dose.…”
Section: Resultsmentioning
confidence: 99%
“…To ensure that we were quantifying staining in axons and not dendritic processes, we made use of microfluidic compartments, which separate axons from the bulk somatodendritic population (Figure 1E) (Niederst et al, 2015; Selfridge et al, 2015; Taylor et al, 2006). Neurons grown in microfluidic devices extend long processes into the axonal space that do not stain for the somatodendritic marker Map2 and that do stain for the axonal marker neurofilament-H (SMI31) (Selfride et al, 2015) (Figure 1E and Figure S1A). We observed that PS1 ΔE9 axons grown in microfluidic devices have decreased axonal APP puncta and APP puncta intensity (Figure 1D); this decrease is sensitive to PS1 ΔE9 gene dose.…”
Section: Resultsmentioning
confidence: 99%
“…After imaging, the time series were qualitatively sorted into (1) positive responses, where axons showed significant repair response following damage, (2) neutral responses, where the growth cones recovered without significant changes in apparent dynamics, and (3) negative responses, where neurons did not recover from damage. These time series were then quantitatively assessed using the wavelet decomposition algorithm, where a region of interest, generally the growth cone, was selected and the wavelet coefficients for each frequency band measured 7 .…”
Section: Methodsmentioning
confidence: 99%
“…All cells with less than 75 percent decrease in activity were independently categorized as having neutral or positive responses. Based on this correlation, the dynamics of the wavelet coefficients were judged to be a meaningful indicator of the overall health and activity of the growth cone 7 . The algorithm was later applied to the measurement and classification of growth cone responses to shock wave damage.…”
Section: Sub-axotomy Studiesmentioning
confidence: 99%
See 2 more Smart Citations